Characterization of the Mycobacterial MSMEG-3762/63 Efflux Pump in Mycobacterium smegmatis Drug Efflux - De Siena, Barbara; Campolattano, Nicoletta; D’Abrosca, Gianluca; Russo, Luigi; Cantillon, Daire; Marasco, Rosangela; Muscariello, Lidia; Waddell, Simon J.; Sacco, Margherita (Frontiers in Microbiology, 2020)
Multi-drug resistant tuberculosis (MDR-TB) represents a major health problem worldwide. Drug efflux and the activity of efflux transporters likely play important roles in the development of drug-tolerant and drug-resistant mycobacterial phenotypes. This study is focused on the action of a mycobacterial efflux pump as a mechanism of drug resistance. Previous studies demonstrated up-regulation of the TetR-like transcriptional regulator MSMEG_3765 in Mycobacterium smegmatis and its ortholog Rv1685c in Mycobacterium tuberculosis (Mtb) in acid-nitrosative stress conditions. MSMEG-3765 regulates the expression of the MSMEG_3762/63/65 operon, and of the orthologous region in Mtb (Rv1687c/86c/85c). MSMEG-3762 and Rv1687c are annotated as ATP-binding proteins, while MSMEG-3763 and Rv1686c are annotated as trans-membrane polypeptides, defining an ABC efflux pump in both M. smegmatis and Mtb. The two putative efflux systems share a high percentage of identity. To examine the role of the putative efflux system MSMEG-3762/63, we constructed and characterized a MSMEG-3763 deletion mutant in M. smegmatis (ΔMSMEG_3763). By comparative analysis of wild type, knockout and complemented strains, together with structural modelling and molecular docking bioinformatics analyses of the MSMEG-3763 trans-membrane protein, we define the protein complex MSMEG-3762/63 as an efflux pump. Moreover, we demonstrate involvement of this pump in biofilm development and in the extrusion of rifampicin and ciprofloxacin, antimicrobial drugs used in first- and second-line anti-TB therapies.